Lucious Cake / Nafisah Moht Yusof Khir ... [et al.] - Moht Yusof Khir, Nafisah; Mohamad, Hasnul Mubaraq; Saini, Shereena; Ismail, Ridzwan; Tayib, Izham Shafaril; Mohd Saleh, Helmi (Faculty of Communication and Media Studies, 2004)
In the present day business environment, we notice that all the entrepreneurs are looking for the new type of product or services in the market that can offer sound financial background, good returns, marketable products, reasonable price and low over heads. LUSCIOUS CAKES is a partnership, which will commence on January 2005. it is a small-sized, Bumiputera owned company that sell cakes comprises of 6 shareholders. Our location is based in Shah Alam.